PENGARUH MARKET VALUE ADDED, RETURN ON ASSETSDAN RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANGTERDAFTARDI BURSA EFEK INDONESIA PERIODE 2013 – 2017 - Maiyaliza, Maiyaliza (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2019)
This study aims to analyze the effect of Market Value Added, Return On Assets and Return On Equity on stock prices. The research object of property and real estate companies is 48 companies. Based on the purposive sampling method, a sample of 15 companies was obtained. The research method uses the classic assumption test and multiple linear analysis. The results of the study show that (1) Market Value Added has an effect on stock prices, because if the company has a higher stock market value than book value it is considered capable of creating wealth for shareholders. (2) Return On Asset does not affect stock prices, because the research sample has a low Return On Asset value, which is caused by a less significant increase in profit compared to an increase in assets. (3) Return On Equity does not affect stock prices, because if the company manages capital well then it can generate profits.